Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Use the functions f(x)=x^2+8x-11,
g(x)=14-2/3x,
and h(x)=x-7
to find f(-4)-f(1)


Sagot :

Answer:

f(-4) - f(1) = -25

Step-by-step explanation:

Knowing that:

f(x) = x² + 8x - 11,

First find f(-4). To do this, substitute -4 in for every x value in the function.

f(-4) = (-4)² + 8-(4) - 11

Square 4.

f(-4) = 16 + 8-(4) - 11

Multiply 8 and -4.

f(-4) = 16 - 32 - 11

Subtract 32 from 16.

f(-4) = -16 - 11

Subtract 11 from 48.

f(-4) = -27

Now find f(1). To do this substitute 1 in for every x value in the function.

f(1) = 1² + 8(1) - 11

Square 1.

f(1) = 1 + 8(1) - 11

Multiply 8 and 1.

f(1) = 1 + 8 - 11

Add 1 and 8.

f(1) = 9 - 11

Subtract 11 from 9.

f(1) = -2

Now take the difference of the results.

f(-4) - f(1) = -27 - (-2) = -27 + 2 = -25.

Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.